Correlation of Platelet-Lymphocyte Ratio (PLR) and Contrast-Induced Nephropathy (CIN) in Patients with ST-Segment Elevation Myocardial Infarction (STEMI) Undergoing Primary Percutaneous Coronary Intervention (PCI) - Steven Winardi; Andika Sitepu (Talenta Publisher, 2021)
Acute Coronary Syndrome (ACS) is a series of clinical disorders caused by acute ischemic heart disease. The clinical spectrum of ACS is unstable angina pectoris (UAP), non ST segment elevation myocardial infarction (NSTEMI) and ST segment elevation myocardial infarction (STEMI). Inflammation occurs from the early stages of atheroma formation to plaque rupture and thrombosis. Thrombocytosis and lymphopenia are associated with the degree of systemic inflammation and the platelet lymphocyte ratio (PLR) is a new marker involving both hematological indices. ST segment elevation myocardial infarction is a type of acute myocardial infarction with high mortality. Management of STEMI patients is carried out with reperfusion therapy consisting of primary percutaneous coronary intervention (PCI) and fibrinolytics. Contrast-induced nephropathy is a serious complication of angiograph procedures that results from administration of contrast media.